Issues of everyday life and social adaptation of Moscow and Moscow region residents in the conditions of evacuation to the Mari ASSR during the Great Patriotic War - O.A. Koshkina; P.O. Lekhanov (Известия высших учебных заведений. Поволжский регион: Гуманитарные науки)
Background. The article examines the issue of evacuation of the civilian popula-tion from Moscow and the Moscow region, the region with the largest number of arrivals to the Mari ASSR during the Great Patriotic War. In the course of the study, attention is drawn to the problems of a domestic nature faced by the evacuees, as well as to the organi-zation of reception, accommodation and further assistance from the republican authorities. The purpose of the work is to study the process of evacuation from Moscow and region to the Mari ASSR, the peculiarities of everyday life and social adaptation. Materials and methods. The sources on this topic are mainly documents identified in the State Archive of the Republic of Mari El. The systematic approach reflects the complexity and connection of the evacuation process with other events of the period, their influence on each other. The principles of historicism and objectivity contribute to the correct analysis and understanding of the phenomenon under study. Results. Strengths and weaknesses in working with evacu-ees were identified. The strengths include a good organization for the reception of refugees, a high degree of employment, and constant attention to improving work with the evacuated population. The weak ones include the material supply of both things and products, inter-ruptions in the work of institutions, and often the unpreparedness of local residents to re-ceive evacuees. Conclusions. Evacuation to the Mari ASSR during the Great Patriotic War was important for saving lives and protecting the population. Of course, this was accompa-nied by a significant number of difficulties, largely due to objective factors of wartime. Moreo-ver, the evacuation contributed to the replenishment of the labor reserve, primarily in industry and agriculture, which also had a certain positive impact on the economy of the region.